Fish diet from Manacapuru Big Lake complex (Amazon): a approach starting from the traditional knowledge - Rebelo, Sérgio Roberto Moraes; Freitas, Carlos Edwar de Carvalho; Soares, Maria Gercilia Mota (Biota Neotropica, 2010)
In the Amazon fishing is one of the main economic activities and higher value to traditional riverine communities of the region. Considering this importance is to suppose that the riverine populations have knowledge about fish fauna explores for them, because their forming culture that maintain a strait relationship with natural resources. This study aim to elevate the traditional knowledge of the fishermen from the riverine communities in the Big Lake Complex about the fish alimentary diet caught for commercialization and consumption. This study was realized in the Manacapuru Big Lake Complex through interview jointed with 62 fishermen. The results presents a detailed knowledge about the tambaqui, tucunaré, pacu, acará-açú, curimatã, aruanã, matrinxã, piranha and pirapitinga fish feeding compatible with the laboratory analyzes and with the specifics literature. Finally the traditional ecological knowledge from the fishermen about the fish ecology in the Big Lake must be used as a subsidy study of lakes management, establishing in this way, an information resource for scientific works at the same time to minimize the cost with a long research.